2021
DOI: 10.1016/j.ijscr.2021.106028
|View full text |Cite
|
Sign up to set email alerts
|

Peroneus longus tendon graft for anterior cruciate ligament reconstruction: A case report and review of literature

Abstract: Introduction The anterior cruciate ligament (ACL) is one of the most frequently injured structures of the knee joint. Anterior cruciate ligament reconstruction (ACLR) provides surgical restoration of the injured ACL using the placement of graft material. The choice of graft is principal in providing optimal knee stability after surgery. Peroneus longus tendon (PLT) is an autograft modality that offers unique benefits for ACL reconstruction cases. Presentation of case We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 16 publications
0
12
0
4
Order By: Relevance
“…AOFAS analysis was 100% at end of 1 year and Wiradiputra et al concluded that peroneus longus can be used as the first option in ACL reconstruction. 20…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AOFAS analysis was 100% at end of 1 year and Wiradiputra et al concluded that peroneus longus can be used as the first option in ACL reconstruction. 20…”
Section: Discussionmentioning
confidence: 99%
“…AOFAS analysis was 100% at end of 1 year and Wiradiputra et al concluded that peroneus longus can be used as the first option in ACL reconstruction. 20 A 2 year follow-up of patients who underwent peroneus longus graft for ACL reconstruction by Sholahuddin observed that excellent IKDC, MCS, Tegner-Lysholm score, AOFAS, FADI scores. Good graft diameter was harvested, thigh hypotrophy was less, with excellent ankle function and a better serial hop test result was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…These studies consistently demonstrate positive results, supporting the viability of autologous peroneus longus tendon graft as a good graft option in reconstructions. [37][38][39][40] In terms of functional results, patients undergoing ACL reconstruction using the peroneus longus tendon autograft achieved excellent scores on several assessment tools, the main ones being the IKDC, Modified Cincinnati, Tegner-Lysholm, AOFAS and FADI scores. 35,41,42 These scores indicate good knee function, ankle stability, and overall patient satisfaction.…”
Section: Peroneus Longus Tendon Autologous Graftmentioning
confidence: 99%
“…Donor ankle activity was not compromised as evidenced by positive scores on ankle function assessment tools and jumping tests. 35,36,40 Another factor that makes the peroneus longus muscle tendon an ideal candidate for ACL reconstruction is that it is technically safe and easy to remove. 46 The tendon is superficially located and its position is not difficult to access by adjacent structures, such as the tendons of the hamstring muscle.…”
Section: Peroneus Longus Tendon Autologous Graftmentioning
confidence: 99%
“…Peroneus longus tendon is an upcoming graft in ACL reconstruction. It demonstrated minimal post-operative morbidity from the ankle donor site because of biomechanical inconvenience [ 2 ].…”
Section: Introductionmentioning
confidence: 99%